Synthetic “smart gel” provides glucose-responsive insulin delivery in diabetic mice - Matsumoto, Akira (Sci Adv, 2017)
Although previous studies have attempted to create “electronics-free” insulin delivery systems using glucose oxidase and sugar-binding lectins as a glucose-sensing mechanism, no successful clinical translation has hitherto been made. These protein-based materials are intolerant of long-term use and storage because of their denaturing and/or cytotoxic properties. We provide a solution by designing a protein-free and totally synthetic material–based approach. Capitalizing on the sugar-responsive properties of boronic acid, we have established a synthetic polymer gel–based insulin delivery device confined within a single catheter, which exhibits an artificial pancreas–like function in vivo. Subcutaneous implantation of the device in healthy and diabetic mice establishes a closed-loop system composed of “continuous glucose sensing” and “skin layer”–regulated insulin release. As a result, glucose metabolism was controlled in response to interstitial glucose fluctuation under both insulin-deficient and insulin-resistant conditions with at least 3-week durability. Our “smart gel” technology could offer a user-friendly and remarkably economic (disposable) alternative to the current state of the art, thereby facilitating availability of effective insulin treatment not only to diabetic patients in developing countries but also to those patients who otherwise may not be strongly motivated, such as the elderly, infants, and patients in need of nursing care.